Procedures and Guidelines for Establishing an E-Commerce Business and Advertising in Electronic Transactions - Moh Ramli; Moh. Karim (Penerbit Hellow Pustaka, 2026)
The development of information technology has driven a significant increase in the growth of e-commerce as a manifestation of digital transformation in the trade sector. E-commerce offers broad opportunities for business actors through ease of transactions and greater market access, but also presents challenges in terms of regulation, consumer protection, and marketing strategy. This article outlines the procedures and methods for building an effective e-commerce business and the digital advertising mechanisms in electronic transactions in accordance with the legal framework in Indonesia. This research uses a literature review method with a normative-descriptive approach. The results confirm that e-commerce success is determined by compliance with business legality, data security, tax compliance, and the implementation of ethical and transparent advertising strategies. Furthermore, advertising in e-commerce functions not only as a medium for product promotion but also as a communication tool to build consumer trust and strengthen brand image. Therefore, the development of e-commerce that is compliant with legal provisions, ethical, and adaptive to technological developments is a key factor in creating a competitive and sustainable digital business climate.